2013
DOI: 10.1002/hipo.22193
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hippocampal neuronal excitability and LTP persistence associated with reduced behavioral flexibility in the maternal immune activation model of schizophrenia

Abstract: Individuals with schizophrenia display a number of structural and cytoarchitectural alterations in the hippocampus, suggesting that other functions such as synaptic plasticity may also be modified. Altered hippocampal plasticity is likely to affect memory processing, and therefore any such pathology may contribute to the cognitive symptoms of schizophrenia, which includes prominent memory impairment. The current study tested whether prenatal exposure to infection, an environmental risk factor that has previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 89 publications
(118 reference statements)
2
31
1
Order By: Relevance
“…In particular, the disruption of hippocampal synaptic integrity may change the electrophysiological properties of hippocampal cells, thereby altering the firing activity of hippocampal neurons. Such abnormalities have indeed been noted by numerous previous investigations using prenatal poly(I:C) models in rodents (Dickerson et al, 2010(Dickerson et al, , 2014Savanthrapadian et al, 2013;Wolff and Bilkey, 2015;Zhang and van Praag, 2015). Furthermore, the synaptic deficits may also contribute to the cognitive impairments that have frequently been observed following prenatal immune activation (reviewed in Boksa, 2010;Harvey and Boksa, 2012;Reisinger et al, 2015).…”
mentioning
confidence: 64%
“…In particular, the disruption of hippocampal synaptic integrity may change the electrophysiological properties of hippocampal cells, thereby altering the firing activity of hippocampal neurons. Such abnormalities have indeed been noted by numerous previous investigations using prenatal poly(I:C) models in rodents (Dickerson et al, 2010(Dickerson et al, , 2014Savanthrapadian et al, 2013;Wolff and Bilkey, 2015;Zhang and van Praag, 2015). Furthermore, the synaptic deficits may also contribute to the cognitive impairments that have frequently been observed following prenatal immune activation (reviewed in Boksa, 2010;Harvey and Boksa, 2012;Reisinger et al, 2015).…”
mentioning
confidence: 64%
“…Using the polyI:C model in rats, Zhang et al (2012) found that MIA impaired strategy set-shifting in the male, but not female, offspring. Findings on reversal learning are mixed with enhancements Zuckerman and Weiner, 2005) and impairments (Han et al, 2011;Savanthrapadian et al, 2013) observed using different task designs. We expected the offspring of polyI:C-treated dams to show impaired PPI, associative recognition memory, crossmodal recognition memory, and behavioral flexibility.…”
Section: Introductionmentioning
confidence: 95%
“…17,18 Many of these changes have also been reported in animal models, including those involving MIA. 19,20 Much previous work in this area has, however, either tended to focus on the HPC as a whole or has focused on the ventral or dorsal regions alone. A more discriminatory approach may be worthwhile, as the dorsal and ventral poles of the HPC are functionally distinct and possess markedly different connectivity with downstream cortical targets including the mPFC.…”
Section: Introductionmentioning
confidence: 99%